Direct affections in the family structure caused by the drug consumption of the patients that attend the CETAD - Torres Aguilar, Ingrid Tatiana (2024)
The research aimed to describe the impact of drug use on the family structure of patients attending the Specialized Treatment Center for People with Problematic Alcohol and Other Drug Use. A qualitative, descriptive, and analytical approach was adopted, and interviews were conducted using a semi-structured guide with five patients in rehabilitation and their family members, in order to obtain a deep interpretation of the situation. The findings highlight how drug use negatively affects relationships within the patients' family structure. Alterations in family dynamics and interactions were observed, underscoring the complexity of the addiction problem. In conclusion, the study highlights the significant influence of the family in the rehabilitation process of patients with addiction problems. The need to integrate the family into the treatment and support of the patients is emphasized, recognizing their crucial role in recovery.